An Undervalued Diagnosis: Post-Traumatic Stress Disorder in the Perinatal Period: A Case Report - Angarita Ramirez, Erika; Maldonado, Jhonier; Varon Arce, Bibian; Suarez Díaz, Monica Julieth; Trejo Varon, Javier Andrés (International Journal of Medical Students, 2023)
BACKGROUND: Perinatal Post-Traumatic Stress Disorder (PTSD) is a disorder that occurs around childbirth, typically after a traumatic birth experience, where women may feel violated due to traumatic childbirth interventions they cannot control. Traumatic birth is defined as an event in which the mother perceives a real or perceived threat to herself or her baby, causing intense fear, helplessness, and horror. This can be considered an obstetric sequel. It is relevant to note that among pregnant women, perinatal PTSD is the third most common psychiatric disorder, with a prevalence ranging from 0.8% to 43% worldwide. Despite its significance, it is little-known, underdiagnosed, and often confused with other conditions such as depression or anxiety. Furthermore, it results in serious family, social, and occupational dysfunctions and is associated with other pathologies. Clinically, women with perinatal PTSD experience symptoms such as re-experiencing the event, detachment from the newborn, nightmares, irritability, and rejection of motherhood. This can lead to consequences for the mother, ranging from a desire not to become pregnant again to severe symptoms such as dissociation, stress, anxiety, and depression. It also affects those close to the mother, such as the partner and family. The aim of this work is to describe perinatal PTSD and emphasize the importance of early identification and appropriate treatment by medical professionals for the benefit of mothers and their children THE CASE: We describe a 35-year-old patient with a history of mixed depressive and anxiety disorder since 2018 experiences perinatal post-traumatic stress disorder. This is related to physical and verbal abuse during her second childbirth, resulting in a traumatic experience. Her childhood was marked by the feeling that her mother favored her younger sister and subjected her to physical and emotional abuse. The first pregnancy was unplanned, and she faced humiliation and abandonment by her partner. Despite the circumstances, the birth was a positive experience. The second pregnancy was planned and desired, but during childbirth in a different clinic from the first, she experienced inadequate care conditions, a lack of privacy, and physical abuse by medical staff. She also received inappropriate comments from the attending gynecologist. During the postpartum period, she shared a room with a cancer patient, complicating her experience. After childbirth, she experienced a hypertensive disorder in the postpartum and chose not to return to the hospital where she gave birth due to her traumatic experiences. Overall, her story reveals a series of challenging experiences related to motherhood that have contributed to her current mental health state. CONCLUSION: Perinatal PTSD is a psychiatric disorder that affects a significant number of pregnant and postpartum women. Its prevalence varies widely, reflecting the need for increased awareness and early detection. Despite its considerable impact on maternal mental health and well-being, perinatal PTSD is often overlooked or confused with other conditions such as depression and anxiety. It's important to raise awareness among medical staff about this disorder and provide a comprehensive and empathetic approach to enhance care for mothers during childbirth and the postpartum period.